ChemInform Abstract: Tetra‐n‐butylammonium Bromide: A Simple but Efficient Organocatalyst for Alcohol Oxidation under Mild Conditions. Issue 45 (23rd October 2014) - Ma, Xinyi; Li, Zhongfeng; Liu, Feijie; Cao, Shengli; Rao, Honghua
Abstract The reaction proceeds with excellent selectivity for secondary benzylic alcohols over aliphatic alcohols or primary benzylic alcohols, respectively.